Salivary duct cyst in the upper lip: Case report and review of the literature - Filipe Nobre Chaves; Francisco Samuel Rodrigues Carvalho; Karuza Maria Alves Pereira; Fábio Wildson Gurgel Costa (Wolters Kluwer Medknow Publications, 2013)
Salivary duct cyst (SDC) in an uncommon lesion of the minor salivary glands, with etiology related to obstruction of the salivary duct. It presents with a color similar to that of the mucosa, is mobile, measures between 3 and 10 mm and affects preferentially the bottom lip, floor of the mouth and the jugal mucosa. SDC have a predilection for the male and individual in elderly groups. The pathogenesis of SDC is associated with the formation of a mucous plug that causes partial or total obstruction of the salivary gland system duct, resulting in the dilation of the duct and increase in intraluminal pressure. They present clinical-pathological characteristics similar to those of salivary gland tumors, making diagnosis difficult and subject to errors in treatment. It is important for the dentist to include SDC in the differential diagnosis of lesions that affect the upper lip, although it is relatively rarely found in this anatomic site.